2021
DOI: 10.3389/frobt.2021.637301
|View full text |Cite
|
Sign up to set email alerts
|

Improved Continuum Joint Configuration Estimation Using a Linear Combination of Length Measurements and Optimization of Sensor Placement

Abstract: This paper presents methods for placing length sensors on a soft continuum robot joint as well as a novel configuration estimation method that drastically minimizes configuration estimation error. The methods utilized for placing sensors along the length of the joint include a single joint length sensor, sensors lined end-to-end, sensors that overlap according to a heuristic, and sensors that are placed by an optimization that we describe in this paper. The methods of configuration estimation include directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 64 publications
(68 reference statements)
4
25
0
Order By: Relevance
“…The purpose of this simulation was to verify the mathematical model of (18). It represents the soft sensor's length when attached to the surface of a toric-shaped soft actuator as mentioned earlier in Section 2.2.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of this simulation was to verify the mathematical model of (18). It represents the soft sensor's length when attached to the surface of a toric-shaped soft actuator as mentioned earlier in Section 2.2.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Interested readers may refer to [9] for an in-depth analysis of forward and inverse kinematics. For soft actuators consisting of a single muscle, at least one sensor is required to sense the extension or bending, as it occurs across one axis only [18,19]. While for soft actuators consisting of multiple muscles, two or more sensors are required to measure the changes, as they occur across multiple axes [20,21].…”
Section: Piecewise Constant Curvature Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To fully understand the contribution of proprioceptive feedback within motor control, we must know which motor and mechanical signals are being transduced by sensors. This is an especially challenging problem for continuum joints in which shape varies continuously [ 14 ], such as that of the fish body during undulatory locomotion. While swimming, the fish’s body curvature varies from head to tail according to the phase of the motor cycle ( Fig 1A ) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A fish must therefore sense and control body angles over its axial length through successive muscle layers that may span up to 10 vertebrae, rather than one or a few dedicated muscle joints [ 16 ]. In robotics, feedback from continuum joints is typically provided by sensing changes in length and curvature [ 14 ]. However, it has recently been demonstrated that stable swimming rhythms can be generated through sensing of hydrodynamic pressures on the body [ 17 ].…”
Section: Introductionmentioning
confidence: 99%